Blood aldosterone level in various types of atrial fibrillation - N. T. Vatutin; A. N. Shevelok; I. N. Kravchenko (Кардиоваскулярная терапия и профилактика)
Aim. To analyse the aldosterone level in the blood of patients with different kinds of atrial fibrillation (AF) and sinus rhythm. Material and methods. Totally, 130 patients included (main group) with AF of non-valvular origin. Of those 40 (30,8%) had permanent, 50 (38,4%) — persistent, and 40 (30,8%) — paroxysmal type of atrial fibrillation. The controls consisted of 40 patients with cardiovascular pathology not having anamnesis of AF. Aldosterone levels were measured by immune-enzyme assay. In paroxysmal and persistent AF the measurement was done before returning to sinus rhythm. Reference ranges for aldosterone were 40-160 pg/ml.Results. Aldosterone level in blood was significantly higher in the main group comparing to controls — mean 141,5±41,8 pg/ml vs 105,0±33,1 pg/ml (р<0,001). The highest level had persisting and paroxysmal AF patients and a little lower in permanent AF patients. Prevalence of hyperaldosteronemia among all patients of the main group was significantly higher comparing to controls, and reached 32,3% and 7,5%, resp., (χ2=8,44, p=0,004), however in multiple analysis the significant differences were revealed only among those with paroxysmal type (47,5%) and sinus rhythm patients.Conclusion. In AF patients aldosterone level is significantly higher comparing to sinus rhythm patients. In addition, the level is significantly higher in paroxysmal and persistent comparing to permanent type.